Mental Health Status of Adolescent Students of Government Schools of Kamrup (Metro), Assam Evidence for Action Plan - Devi, Nirada; Barthakur, Sangeeta; Das, Dulumoni (JOURNAL OF INDIAN EDUCATION, 2021)
Child and adolescent mental health is a crucial issue worldwide in the present times. This study is aimed at assessing the prevalence of mental health issues and its determinants among the adolescents studying in government schools of Kamrup (Metro) district of Assam, a north eastern state of India. The data collected from 1839 randomly chosen students from 101 government schools have been assessed on the basis of scores obtained in the standard GHQ- 28 study tool and subsequent statistical analysis. The results suggest an overwhelming presence of psychological distresses among the adolescents, the proportion being more in girls than boys. Academic proficiency of students and occupations of fathers showed significant association with the levels of mental health problems (p-value<0.05). Categorical analysis of manifested symptoms revealed that more than 80% of the adolescents suffered from somatic symptoms followed by anxiety and insomnia (66%). As unaddressed adolescent mental problems continue onto adulthood, hence it is of utmost importance that due cognizance is given to this problem by the concerned authorities. Some triggering factors have been identified and remedial measures suggested, in this study.